MAJORITY DECODER OF CYCLIC CODE WITH TWO-STAGE ESTIMATION OF RELIABILITY OF INFORMATION - A. I. Korolev; V. K. Konopelko; N. A. Salas; E. G. Makeichik; K. I. Pirogov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The efficiency two-stage majority decoding algorithm for cyclic codes in the correction of error of multiplicity binary symbols where - the number of test equations, needed to guarantee the correction of erroneous symbols is studied. The conditions under which correction of erroneous symbols of multiplicity where is executed, are analyzed, and also the lower bound of the number of combinations of corrected errors of multiplicity and binary symbols is identified for the 2 bits correcting BHC-code. The erroneous decoding probability of the two-stage majority decoder in presence of a communication channel with the additive white Gaussian noise (AWGN) is defined.